Development of the SITASYA (Solar System) Media Box to Minimize Elementary School Students' Misconceptions - Maya Qharisma Agustin; Anatri Desstya (Universitas Muhammadiyah Surakarta, 2025)
Science instruction in elementary schools plays a crucial role in developing students' understanding of the universe. The solar system is abstract and requires media that can visualize concepts for easy comprehension. However, the use of media in the learning process is limited, leading to misconceptions among students. Learning media that focuses on minimizing misconceptions remains rare. This study aims to: a.Describe the urgency of developing the SITASYA Box media on the solar system material to minimize misconceptions; b) Test the validity of the SITASYA Box media on the solar system material; c)Knowing the practicality of the SITASYA Box media on the solar system material according to science teachers. This type of research is a Research and Development (R&D) study with a 4-D development model (define, design, development, and disseminate), which is limited to the development stage. The subjects of this study were teachers and students of grade VI MI Muhammadiyah Gonilan and expert validators. Data collection techniques were carried out through interviews, observations, tests, and product validation sheets. Data analysis techniques were carried out qualitatively and quantitatively descriptively. The results of the study indicate that: 1) The urgency of this research is characterized by the condition that the learning media used has not been able to visualize concepts dynamically and proportionally so that it has the potential to cause misconceptions in students; 2) The validity of the SITASYA Media Box is stated